Investigation on the undrained shear strength of soft clay mixed with various percentages of lime and 6 % of silica fume - Leong, Kah Seng (2015)
Soil stabilization can make the soils becoming more stable. This method is applying admixture on the soil. Lime stabilization enhances engineering properties of soil, including reducing the soil plasticity, increase in optimum moisture content, decrease in maximum dry density and improvement in compaction of soil. Silica fume is utilized as a pozzolanic material in the application of soil stabilization. Silica fume was once considered as non-environmental friendly. Now, it has been adopted as a binder material with cement materials for the application of the soil stabilization. In this research, the materials required are kaolin grade S300, lime and silica fume. The focus of the study is the determinations of the physical properties of the soils tested and the strength of kaolin mixed with 6 % of silica fume and various percentages (3.0 %, 5.0 %, 7.0 % and 9.0 %) of lime. Unconfined compression test is carried out on the kaolin and the mixtures of soil-lime-silica fume to investigate the effect of lime stabilization with silica fume additives on the unconfined compressive strength of the mixtures. Based on the results obtained, all soil samples are indicated as soils with medium plasticity. From 0 % to 9.0 % of lime with 6.0 % of silica fume, the decrease in the maximum dry density is by 5.92 % and the increase in the optimum moisture content is by 23.5 %. Decreases in the coefficient of permeability of the mixtures occur if compared to the coefficient of permeability of kaolin soft clay itself. The optimal percentage of lime-silica fume combination is attained at 5.0 % of lime and 6.0 % of silica fume in order to improve the shear strength of kaolin soft clay. The improvement in shear strength of this stabilized mixture is 29.83 % if compared to the shear strength of the kaolin sample. It can be concluded that lime-silica fume mixture was an effective stabilizer for improving the geotechnical properties of clayey soils.